Taxonomic clarifications, a new combination, and three new species of Neotropical Rinorea (Violaceae) - Saúl E. Hoyos-Gómez; Harvey E. Ballard Jr.; Ricardo Callejas Posada; Gregory A. Wahlert (PhytoKeys)
Based on findings of revisionary studies of Neotropical Rinorea, we propose several taxonomic novelties and clarifications in this study, including the description of three new species, a new combination, the placement of three species in synonymy, and updated descriptions of two poorly known species from South America. One of the new species, Rinorea idarragae, is described from Mesoamerica and belongs to R. sect. Rinorea. The two other new species are from South America and are placed in R. sect. Pubiflorae: Rinorea cardenasii occurs in the region of the western edge of the Guiana Shield in Colombia, and Rinorea pabongonzaleziorum is from the Amazon Basin in Colombia and Venezuela. Rinorea lindeniana var. fernandeziana is elevated to the rank of species, and Rinorea cordata, R. antioquiensis, and R. hymenosepala are synonymized under R. laurifolia, R. squamata, and R. ulmifolia, respectively. Finally, we provide updated descriptions of Rinorea deflexa from Ecuador and Peru and Rinorea bicornuta from Colombia and Brazil. For the three new species, we provide descriptions, illustrations, distribution maps, and preliminary conservation assessments based on IUCN Red List categories and criteria.